Acute Myocardial Infarction among Young Adults in India: Clinical Profile and Risk Factors - Mulay Surekha P, Mulay Pramod Pz; Milind S, Hanchate (International Journal of Innovative Research in Medical Science, 2017)
Introduction: The growth of cardiology as a specialty may be explained by a study of the attention given to acute myocardial infarction. The incidence of coronary artery disease and acute myocardial infarction has been recognized in the younger age group more frequently in the recent years. Increasing frequency among young individuals has led to the entitling "Coronary artery disease in young (CADY)". Present study was done to study the IHD in young patients with objectives to study the (1) clinical profile of myocardial infarction in young patient of age group 45 years and below and (2) conventional and newer risk factors for myocardial infarction in young age. Material & Methods: Present study was a hospital based descriptive study conducted in a tertiary care hospital of Mumbai. Total 45 patients of acute myocardial infarction of age group 45 years and below, were studied with reference to clinical profile and risk factor analysis. Results: In present study out of 45 patients more than 80% were male, 35% were in the age group of 41-45 years and only 6% were below 30 years age. In the present study 46% of patients belonged to physically more active group. In the present study the highest incidence of infarction was in social class II and III constituting 66.67%. Smoking was one of the important risk factors for AMI in this study, present in 55.56% of patients. Type-A personality was noted in 16 patients (35.36%). Apart from conventional risk factors two cases of structural aortic disease, one case each of increase dLp(a) level, Hyperhomocysteinemia and protein-c deficiency had been noted as risk factors as newer risk factors. Conclusions: In young patients with AMI majority of the patients belong of the age group between 36-45 years. Newer risk factors are commonly associated with AMI at young age.